Come on children - Hamilton, John ca. 20. Jh; Živojinović, Aleksandar 1953-; Zaza, Jack ca. 20. Jh (<<The>> Criterion collection, 2010)
"Ten teenagers journey down a path to self-discovery as they adjust to life on a farm in this examination of the stress and alienation of adolescence." [imdb.com]
Original: Kanada 1973
Bildformat 1.66:1 (16:9)
Keywords: Bauernhof; Selbsterfahrung; Identitätsfindung; Jugend; Film; DVD-Video